Examining Views of Police Chiefs and College Students Regarding Drug Disqualifiers for the Hiring of Police Officers in Arizona - Bottema, A. Johannes (Journal of drug issues, 2021)
Police applicant disqualification due to prior illegal drug use is a contributing factor to major recruitment and hiring challenges currently facing many American policing agencies. This article explores how chief executives of law enforcement agencies and college students enrolled in criminology courses in Arizona view current statewide police hiring standards related to prior drug use. We use surveys conducted in cooperation with the Arizona Peace Officer Standards and Training Board to examine respondent opinions regarding the preemployment use of marijuana and illicit use of prescription drugs. Generally, we find significant differences between the chief executive and student views. Students, who represent potential policing applicants, typically are in favor of harsher treatment of prior drug use than chief executives, although students are also more open to forgiving marijuana use under certain circumstances. We discuss the implications of these findings for police hiring and suggest potential areas of policy change.